2022
DOI: 10.1002/hrm.22115
|View full text |Cite
|
Sign up to set email alerts
|

The HR ecosystem framework: Examining strategic HRM tensions in knowledge‐intensive organizations with boundary‐crossing professionals

Abstract: In this article, we use Snell & Morris' (2021) new HR ecosystem framework to empirically examine strategic fit and alignment tensions for knowledge‐intensive organizations and professional knowledge workers. Rich data were collected through in‐depth interviews with 75 members of faculty engaged in knowledge‐intensive work for Business and Management Schools (B&M), and the analysis of strategy documents. The application of the framework enables us to contribute to dynamic capabilities theory and SHRM in four wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 102 publications
0
1
0
Order By: Relevance
“…Similarly, Donnelly and Hughes (2023) found that when top‐level managers engage with mid‐level managers to refine and develop strategy, members of the organization are more likely to contribute to the development of bottom‐up strategies. Even though this creates constant tension within the work ecosystem, it allows for strategies to evolve.…”
Section: Trends Shaping the Ecosystem Of Work And Organizationmentioning
confidence: 97%
“…Similarly, Donnelly and Hughes (2023) found that when top‐level managers engage with mid‐level managers to refine and develop strategy, members of the organization are more likely to contribute to the development of bottom‐up strategies. Even though this creates constant tension within the work ecosystem, it allows for strategies to evolve.…”
Section: Trends Shaping the Ecosystem Of Work And Organizationmentioning
confidence: 97%